A Review: Effects Of Mussel Shell Ash As Concrete Mixture Under Sodium Chloride Exposure - Ishak, Muhammad Nur Fitri; Othman, Nor Hazurina; Sainudin, Muhammad Shabery (Recent Trends in Civil Engineering and Built Environment, 2021)
This research involves a review on effects of mussel seashell mixture concrete on curing in sodium chloride. Among the problems that can be identified is that seashells waste such as mussel seashell has been dumped into landfills. Seashell skin is one of the recyclable waste materials. From a scientific point of view, such waste can be seen to have mineral elements found in the element cement which is calcium carbonate (CaCO3) which is more than 90% calcium carbonate. Therefore, the focus of the previous review studies focuses on the use of solid waste from the seashells. In every review research of the study, shells have the potential to be a mixture or substitute in concrete. In a review of the study conducted, there are 50 articles that have been referred to get the optimal percentage for seashells mixture which this percentage can be used in subsequent studies. This review is done based on previous study on laboratory test including compression strength tests, tensile strength tests and density. For the physical properties of the seashells were studied based on the analysis of specific gravity and chemical composition from the previous review studies. From a previous review study, the use of seashells has the potential to be a mix in concrete to improve compressive strength, density and tensile strength. Once researched, it also has a high capacity or equivalent to ordinary conventional concrete that is exposed to aggressive environments such as seawater (whose main chemical composition is high sodium chloride). This previous review study is focused on 28 days curing and mussel seashell. Among of this previous review study, can conclude that the optimum percentage of seashells as cement mixture is between 2 – 3% for the compressive strength, 2-4% for the density and 2-6% for the tensile strength. Optimum percentage for curing for 28 days is 2.37% concentrated of sodium chloride (NaCl) with 1% of mixture for mussel seashells in concrete.